PERANCANGAN ALAT PENGUKUR DENYUT JANTUNG MENGGUNAKAN PULSE SENSOR DAN LCD BERBASIS ARDUINO UNO ATMEGA 328 - anwar fattah; ginanjar putra wardana (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
The heart is one of the main organs in the human body. Normal human heart rate ranges between 60-100 beats per minute. One way to know a person's heart condition is by calculating the heart rate. To know the frequency of the heartbeat we can calculate the manual way that is by putting the tip of the index finger and middle finger on the base of the thumb on the wrist, knee fold, groin, or side of the throat. Calculate heart rate for 15 seconds and multiply this by 4 to determine the heart beats per minute. Design of this tool is expected to make easier the calculation of heart rate with accurate measurement accuracy and can detect heart conditions based on heart rate calculation results. Arduino Uno Atmega 328 and LCD (Liquid Crystal Display) based pulse meter use Pulse Sensor to detect heart rate. Heartbeat data will be processed by Arduino and the results are displayed on the LCD. This study aims to make easier the calculation of the pulse and detect heart conditions.The research held on April until June 2017 at Laboratorium Teknik Elektro Universitas Balikpapan. The study focused to design the heart pulse measurement. Once designed, the tool need to be tested each block of the tool and then whole tool. The result of the tool and the result by manual count got the average value of the difference or error amount 1,2%. Based on the average value of the difference or error can be concluded that the heart rate measuring tool that has been made to work with the exact measurement accuracy